DINAMIKA KELEKATAN ANAK USIA DINI PADA KELUARGA LONG DISTANCE MARRIAGE (Studi Kasus pada Salah Satu Keluarga di Kecamatan Banyubiru Kabupaten Semarang) - Zulfa Nisrina Bilqis; Gia Nikawanti; Dhea Ardiyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the phenomenon of Long Distance Marriage, which places young children in physical separation from one parent and may affect attachment formation. This study aims to describe parenting styles, parental roles in caregiving, and the form of children’s attachment to their parents in a Long Distance Marriage family. It employs a qualitative approach using a single case study method on one family in Banyubiru Subdistrict, Semarang Regency, whose father works in the shipping sector. Data were collected through observation, documentation, and field notes over five sessions, then analyzed using the Miles, Huberman, and Saldana model, with data validity ensured through technique and time triangulation. The findings reveal three points. First, the dominant parenting style applied is the authoritative (democratic) style. Second, caregiving roles are carried out collaboratively, with the mother as the primary caregiver, the father maintaining his emotional role through long-distance communication, and the grandparents as substitute caregivers. Third, the most dominant attachment pattern is secure attachment, formed toward the mother and grandmother and maintained toward the father. The study concludes that Long Distance Marriage does not automatically cause insecure attachment, as long as a responsive primary caregiver, consistent communication, and family network support are available.